PHIALOMYCES MACROSPORUS REDUCES CERCOSPORA COFFEICOLA SURVIVAL ON SYMPTOMATIC COFFEE LEAVES - Laborde, Marie Caroline Ferreira; Botelho, Deila Magna dos Santos; Rodriguez, Gabriel Alfonso Alvarez; Resende, Mário Lúcio Vilela de; Queiroz, Marisa Vieira de; Batista, Aline Duarte; Cardoso, Patrícia Gomes; Pascholati, Sérgio Florentino; Gusmão, Luis Fernando Pascholati; Martins, Samuel Júlio; Medeiros, Flávio Henrique Vasconcelos de (Coffee Science - ISSN 1984-3909, 2019)
Saprobe fungi and necrotrophic pathogens share the same niche within crop stubble and the search for fungi non-pathogenic to plants that are able to displace the plant pathogens from its overwintering substrate contributes to the disease management. Brown eye spot (Cercospora coffeicola) is among the most important coffee diseases, it is caused by a necrotrophic pathogen that has decaying leaves as its major source of inoculum. We have screened saprobe fungi for the ability to reduce C. coffeicola sporulation and viability and determined the possible mechanisms involved in the observed biocontrol. A selected saprobe fungus, Phialomyces macrosporus, reduced the pathogen’s viability by 40% both in vitro and in vivo. The fungus acts through antibiosis and competition for nutrients. It produced both volatile and non-volatile compounds that inhibited C. coffeicola growth, sporulation, and viability. It also produced the tissue maceration enzyme (polygalacturonase), which reduces the pathogen both in detached leaves or in planta. The reduction in the fungal viability either by the saprobe fungus or its polygalacturonase-fraction supernatant resulted in the reduction of the disease rate. Therefore, P. macrosporus is a potential microbial agent that can be used in an integrated management of brown eye spot through the reduction of the initial inoculum of the pathogen that survives and builds up in infected leaves.